2009
DOI: 10.3750/aip2009.39.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity and condition of successful invaders: <I>Siganus rivulatus</I> and <I>S. luridus</I> (Actinopterygii: Perciformes: Siganidae) in the eastern Mediterranean Sea

Abstract: Condition exhibited a clear seasonal trend for the two rabbitfishes. It increased in spring prior to the reproduction period and again in autumn before the decrease of seawater temperature, and remained low during the cold period. Its values were significantly higher for S. luridus than to S. rivulatus. Conclusion. S. rivulatus displayed a higher fecundity while S. luridus showed a better condition in the Eastern Mediterranean. Gonad mass was the best predictor of fecundity for both species while condition exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, the fecundity of fish is mostly related to biological factors; Length, weight, and age (Nikolsky, 1963;Bagenal, 1978). Bariche et al (2003) Lebanese coast, Mediterranean 12.6-25.2 -250,000 El-Far 2008Alexandria, Mediterranean 14.4-20 64,292-380,772 - Bariche et al (2009) Eastern There were positive relationships between the number of eggs and both total length and body weight at all study regions. The relative fecundity increased with increasing length at all studied areas, and showed fluctuations in its relation with the body weight in agreement with observation of Elfar (2008), this fluctuation may be attributed to the presence of each variation in the well-being which may cause fluctuation in eggs number in its relation with weight (Oso et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the fecundity of fish is mostly related to biological factors; Length, weight, and age (Nikolsky, 1963;Bagenal, 1978). Bariche et al (2003) Lebanese coast, Mediterranean 12.6-25.2 -250,000 El-Far 2008Alexandria, Mediterranean 14.4-20 64,292-380,772 - Bariche et al (2009) Eastern There were positive relationships between the number of eggs and both total length and body weight at all study regions. The relative fecundity increased with increasing length at all studied areas, and showed fluctuations in its relation with the body weight in agreement with observation of Elfar (2008), this fluctuation may be attributed to the presence of each variation in the well-being which may cause fluctuation in eggs number in its relation with weight (Oso et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…Other studies manipulated different aspects in the reproduction of S. rivulatus in the Red Sea such as; seasonal changes in the ovaries (Amin, 1985a) and reproductive cycle of males in Jeddah (Amin, 1985b). At the Mediterranean coast of Lebanon, George (1972) studied their breeding and movements while Bariche et al (2003;2009) studied sex ratio, maturity stages, length at first sexual maturity, gonadosomatic index (GSI) and fecundity. In Egypt, some studies were performed on the reproductive biology of S. rivulatus from Alexandria such as; sex ratio, gonadosomatic index (GSI), length at first sexual maturity, ova diameter, fecundity and time of spawning (Hussein, 1986;Fahmy, 2019;El-Far, 2008).…”
mentioning
confidence: 99%
“…Both Siganus luridus and Siganus rivulatus are very fecund, potentially producing more than 250,000 eggs per spawning season (Bariche et al, 2009) and with a surface planktonic larval period that may last up to four weeks (Woodland 1999); potentially therefore, surface currents may transport larvae for up to 1000 km (Azzurro et al, 2006). Moreover, adult siganids may disperse by active swimming, perhaps in association with drifting weed (Azzurro et al, 2006 and references therein Shakman (2008) has suggested that competition between the two siganids may account for his observations that Siganus luridus is more abundant in the Gulf of Sirte (also known as the Gulf of Sidra) and the western Libyan coast whereas Siganus rivulatus is more abundant along the eastern Libyan coast.…”
Section: Discussionmentioning
confidence: 98%
“…Siganus rivulatus (Forsskål, 1775) and Siganus luridus (Rüppel, 1829) The most successful invaders in the Mediterranean Sea include the two rabbitfishes, Siganus rivulatus (Forsskål, 1775) and Siganus luridus (Rüppell, 1829). Both are Indo-Pacific species (Bariche et al, 2009). The marbled spinefoot S. rivulatus was firstly recorded in the Mediterranean in 1924 (Steinitz, 1927) while the dusky spinefoot S. luridus was recorded for the first time in 1955 (Ben-Tuvia 1964).…”
Section: Sargocentron Rubrum (Forsskål 1775)mentioning
confidence: 99%